2015
DOI: 10.2298/gensr1503051c
|View full text |Cite
|
Sign up to set email alerts
|

New data on sterlet (Acipenser ruthenus L.) genetic diversity in the middle and Lower Danube sections, based on mitochondrial DNA analyses

Abstract: Poor regulated fishery, pollution, fragmentation and loss of habitat are most important factors influencing decline of sterlet population worldwide. In Middle and Lower Danube region, this species still have significant economic importance since wilde populations are commercially exploited, while Upper Danube populations are dependent on stocking efforts in order to maintain their presence in open waters. Aim of present study is to analyze genetic diversity of sterlet populations from the Mid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Overall, the recovered mitochondrial diversity of sterlet population in the Middle Danube (Slovak-Hungarian stretch) is comparable with other parts of the river (e.g. Reinartz et al, 2011;Cvijanović et al, 2015), but within three groups, particularly for the more variable CYTB, a notable difference in the number of haplotypes was observed (W À 8, F1 -5, S À 2). Although with almost the lowest size, the WILD group had the highest number of haplotypes.…”
Section: Microsatellitesmentioning
confidence: 51%
See 1 more Smart Citation
“…Overall, the recovered mitochondrial diversity of sterlet population in the Middle Danube (Slovak-Hungarian stretch) is comparable with other parts of the river (e.g. Reinartz et al, 2011;Cvijanović et al, 2015), but within three groups, particularly for the more variable CYTB, a notable difference in the number of haplotypes was observed (W À 8, F1 -5, S À 2). Although with almost the lowest size, the WILD group had the highest number of haplotypes.…”
Section: Microsatellitesmentioning
confidence: 51%
“…The genetic data acquired within recent studies (e.g. Cvijanović et al, 2015;Fopp-Bayat et al, 2015;Chassaing et al, 2016) clearly show that well-managed and urgent actions are needed if we want to prevent their extinction. Among other actions including the restoration of key habitats and reopening of closed migrations routes, a wellmanaged stocking program is needed.…”
Section: Microsatellitesmentioning
confidence: 99%
“…Based on available data, during the mid-twentieth century, research of sturgeons in the Western Balkans was oriented to life history, biology, and ecology (Janković 1958;Ristić 1963aRistić , b, c, 1967aRistić , b, c, d, 1969a. Due to lack of different sturgeons species, as a consequence of Iron Gate dams construction, as well as lack of funding, later research was focused on sterlet morphometry, pollution assessment, and genetic (Jarić et al 2011c;Lenhardt et al 2012Lenhardt et al , 2014Cvijanović et al 2015Cvijanović et al , 2017, i.e., more laboratory-oriented research. In the last decade, development of population models and extinction models (Jarić et al 2009a(Jarić et al , 2010(Jarić et al , 2014(Jarić et al , 2016Simić et al 2014) provided tools for decision makers to adapt conservation measures.…”
Section: Discussionmentioning
confidence: 99%
“…At the beginning of the twenty-first century, number of publications concerning sturgeons and their protection in Western Balkans rapidly increased (Lenhardt et al 2004(Lenhardt et al , 2005a(Lenhardt et al , 2006a(Lenhardt et al , 2009(Lenhardt et al , 2012(Lenhardt et al , 2014Jarić et al 2009aJarić et al , b, 2010Jarić et al , 2011aJarić et al , b, c, 2014Jarić et al , 2015Smederevac-Lalić et al 2011;Cvijanović et al 2015Cvijanović et al , 2017. Although beluga, Russian sturgeon, Atlantic sturgeon, and ship sturgeon are investigated (Lenhardt et al 2005a(Lenhardt et al , 2006aJarić et al 2009bJarić et al , 2011a, main focus was on sterlet (Lenhardt et al 2004(Lenhardt et al , 2009(Lenhardt et al , 2012Ognjanović et al 2008, Jarić et al 2011cCvijanović et al 2015Cvijanović et al , 2017, with nonindigenous paddlefish (Polyodon spathula) and Siberian sturgeon (Acipenser baerii) also subject of interest (Lenhardt et al 2006b;Jarić et al 2019;Govedič and Friedrich 2018). Sterlet survey in the Danube River, between 2002-2003 (Lenhardt et al 2004) showed shift of length-frequency distribution toward lower length classes, as well as decrease in sterlet catch.…”
Section: Sturgeons Research (And Conservation Assessment) In Western ...mentioning
confidence: 99%
See 1 more Smart Citation